2019
DOI: 10.1002/mds.27886
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin for Rapid Eye Movement Sleep Behavior Disorder in Parkinson's disease: A Randomised Controlled Trial

Abstract: A B S T R AC TBackground: Melatonin may reduce REM-sleep behavior disorder (RBD) symptoms in Parkinson's disease (PD), though robust clinical trials are lacking. Objective: To assess the efficacy of prolonged-release (PR) melatonin for RBD in PD. Methods: Randomized, double-blind, placebocontrolled, parallel-group trial with an 8-week intervention and 4-week observation pre-and postintervention (ACTRN12613000648729). Thirty PD patients with rapid eye movement sleep behavior disorder were randomized to 4 mg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 32 publications
0
104
2
1
Order By: Relevance
“…However, a recent placebo-controlled trial found melatonin use at either 2 or 6 mg/night improved self-reported measures such as daytime sleepiness, sleep quality or dream enactment behaviors ( 105 ). A recent randomized, controlled trial of melatonin in a cohort of PD patients with RBD also found no effect of melatonin on RBD symptom frequency or severity ( 106 ), suggesting melatonin may be less effective at controlling RBD symptoms in the context of advanced neurodegeneration. The efficacy of melatonergic compounds such as the melatonin receptor agonist Ramelteon also do not significantly improve RBD symptom severity ( 107 ).…”
Section: Pharmacologicalmentioning
confidence: 99%
“…However, a recent placebo-controlled trial found melatonin use at either 2 or 6 mg/night improved self-reported measures such as daytime sleepiness, sleep quality or dream enactment behaviors ( 105 ). A recent randomized, controlled trial of melatonin in a cohort of PD patients with RBD also found no effect of melatonin on RBD symptom frequency or severity ( 106 ), suggesting melatonin may be less effective at controlling RBD symptoms in the context of advanced neurodegeneration. The efficacy of melatonergic compounds such as the melatonin receptor agonist Ramelteon also do not significantly improve RBD symptom severity ( 107 ).…”
Section: Pharmacologicalmentioning
confidence: 99%
“…Some studies have shown that some lifestyle interventions could improve the quality of life of PD patients, such as behavior therapy, sleep improvement, mood improvement, and physical exercise (2)(3)(4)(5). However, few studies have examined the effect of nutritional status on the quality of life of patients with PD (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, a clinical consensus recommended the use of melatonin in RBD at level B (Aurora et al, 2010). However, a negative result was recently published in a randomized, double-blind, placebo controlled, parallel-group trial of 30 RBD patients treated unsuccessfully for 8°weeks with 4 mg prolonged release melatonin (Gilat et al, 2020). Therefore, more high-quality studies are needed in this respect.…”
Section: Clinical Use Of Melatonin In Parkinson's Disease and Rbdmentioning
confidence: 99%